2020
DOI: 10.1038/s41598-020-74866-4
|View full text |Cite
|
Sign up to set email alerts
|

Combination of syringaresinol–di–O–β-d-glucoside and chlorogenic acid shows behavioral pharmacological anxiolytic activity and activation of hippocampal BDNF–TrkB signaling

Abstract: Mental stress, such as anxiety and conflict, causes physiological changes such as dysregulation of autonomic nervous activity, depression, and gastric ulcers. It also induces glucocorticoid production and changes in hippocampal brain-derived neurotrophic factor (BDNF) levels. We previously reported that Acanthopanax senticosus HARMS (ASH) exhibited anxiolytic activity. Thus, we attempted to identify the anxiolytic constituents of ASH and investigated its influence on hippocampal BDNF protein expression in male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Moreover, our results showed that apigenin boosted the antioxidant capacity of the neural cells exposed to MSG via enhancing the antioxidant enzymes. These ndings corroborate with previous authors (Al Olayan et al 2020, Lim et al 2018, Mishra &Goel 2013, Miyazaki et al 2020). In former studies, apigenin was reported to upregulate the expression of nuclear factor E2related factor 2 (Nrf2)/heme oxygenase (HO-1) signaling pathways (Mishra &Goel 2013, Taskiran &Ergul 2021).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Moreover, our results showed that apigenin boosted the antioxidant capacity of the neural cells exposed to MSG via enhancing the antioxidant enzymes. These ndings corroborate with previous authors (Al Olayan et al 2020, Lim et al 2018, Mishra &Goel 2013, Miyazaki et al 2020). In former studies, apigenin was reported to upregulate the expression of nuclear factor E2related factor 2 (Nrf2)/heme oxygenase (HO-1) signaling pathways (Mishra &Goel 2013, Taskiran &Ergul 2021).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, apigenin possess another free radical-scavenging site; m-5,7-dihydroxy arrangements in A ring and 4-oxo group in C ring (Kazmi et al 2020). Further, scavenging excess free radicals may rely on the existence of C2-C3 double bond and 4 keto group in C ring that are involved in electron transfer from B ring (Miyazaki et al 2020). Moreover, our results showed that apigenin boosted the antioxidant capacity of the neural cells exposed to MSG via enhancing the antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Samad et al [ 26 ] demonstrated the protective effect of gallic acid against arsenic-induced anxiety- and depression-like behaviors and memory impairment in male rats. Miyazaki et al [ 27 ] demonstrated that chlorogenic acid showed behavioral pharmacological anxiolytic activity and activation of hippocampal BDNF-TrkB (brain-derived neurotrophic factor and tropomyosin receptor kinase B) signaling. Rosmarinic acid exhibited anxiolytic effects in a beta-amyloid 1-42 (Aβ1-42)-induced mouse model of Alzheimer’s disease as reported by Mirza et al [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified chlorogenic acid and syringaresinol-di-O-β-D-glucoside (SYG) as bioactive components of Acanthopanax . Chlorogenic acid and SYG increases hippocampal BDNF protein levels, activates hippocampal BDNF signaling, therefore, the anti-depressive effects of Acanthopanax may be through the regulation of BDNF expression and its downstream signaling ( Miyazaki et al, 2020 ).…”
Section: Molecular Mechanism Of Action Of Sg Antidepressantsmentioning
confidence: 99%